(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2025)
Air pollution is a major concern worldwide especially in developing countries like Bangladesh due to rapid industrial growth and unplanned urbanization. Despite being the country’s commercial hub, Chattogram has not been sufficiently studied in terms of air pollution. This research aims to address this gap by determining the trend of air pollutants and identifying their sources in Chattogram. Using satellite-based remote sensing data from Sentinel-5 TROPOMI, spatial and seasonal changes of six air pollutants: Nitrogen dioxide, Sulfur dioxide, Carbon Monoxide, Formaldehyde, Methane, and Aerosol have been observed for the years 2019 to 2023. Moreover, qualitative surveys with local residents and industrial workers were done to compare the consistency of the results and the perceived impact of relevant stakeholders. The trends show overall increasing concentrations for all the pollutants over the years notably near the industrial areas and seaport of Chattogram with a decline during the COVID-19 pandemic suggestive of reduced industrial activities. The concentrations in the dry seasons were higher than in the wet seasons and the qualitative survey revealed that the industrial workers perceived air pollution as more severe than the residents. The growing trend of air pollutants and the community perceptions obtained from this research highlight the need for continuous monitoring of the air quality, demarking the high concentration pollution zone, targeting measures for reducing emission at-source and sustainable agricultural practices. Recognizing the threat, and coordinating public and private efforts are crucial to mitigating air pollution emissions and ensuring a better future for the upcoming generations. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 13(2), 2024, P 107-124